Engineering Properties of Oil Palm Shell (OPS) Hybrid Concrete for Lightweight Precast Floor Slab - Ng, C.H. (International Conference on Sustainable Construction Materials and Technologies, Coventry University and The University of Wisconsin Milwaukee Centre for By-products Utilization, 2007)
An experimental study on the engineering properties of OPS hybrid concrete for precast floor slab was conducted. Conventional crushed stone as partial replacement of OPS was employed. Three conditions of curing to simulate the laboratory curing condition, practical curing condition, and without curing are applied. The slump, demoulded density, compressive strength, flexural strength, splitting tensile strength and modulus of elasticity were determined. OPS concrete with 30% crushed stone as coarse aggregate fulfilled the minimum strength requirement for lifting/transportation and at service. Since the air dry density of this concrete is 2000 kg/m3, it can be accepted as lightweight concrete. Hence, OPS hybrid concrete with crushed stones can be used to manufacture lightweight precast floor slab. The results of this ongoing research on the potential use of OPS concrete for lightweight precast floor slabs are reported